The Evaluation Sustainability Strategy in Independent Power Producer PT XYZ - Rahadi Rahadi; Dwi Hartanti (Dinasti International Journal of Education Management and Social Science, 2025)
evaluates the sustainability strategy and its implementation in PT XYZ, a private power producer in Indonesia. The aim is to assess the strength of the strategy and to examine how far it is executed at the organizational level. A qualitative single case study uses internal document analysis with key personnel in economic, social, environmental, and governance functions. Strategy is assessed with framework of Wardhani and Rahadian, while implementation is analyzed using the strategy execution principles of Thompson et al. The results show that PT XYZ fulfils 85 percent of strategy indicators, with strengths in stakeholder engagement, strategic view, and economic and social strategies, but implementation reaches only around 40 percent because governance, leadership, staged planning, and sustainability culture remain weak. that PT XYZ must strengthen organizational capabilities to narrow the gap between strategy design and execution.